Using games to improve the vocabulary acquisition with students of 2 nd year of basic education at “Carlos Burneo Arias” school. Academic year 2013 - 2014 - Córdova Jumbo, Karen Paola (2015)
This action research investigated the use of games in the improvement of vocabulary learning with 2nd year students at Carlos Burneo Arias public school. A twelve-session intervention plan was implemented to improve the skill. The general objective of the present research work is: To use games in order to improve the vocabulary acquisition with students of 2nd Year of Basic Education at “Carlos Burneo Arias” School in the Academic Year 2013 - 2014. A researcher – made test was designed and used to measure the seven students’ progress and perception of games use. Additional instruments like observation sheets, and a researcher’ field diary were also used every session to see the students’ progress. The results indicated that the use of games facilitated meaningfully the improvement of vocabulary, which was reflected in the noticeable increase of the post-test scores and students’ progress during the intervention. In conclusion, this study helped students to improve their vocabulary learning, the researcher to sharpen her teaching skills and the community to have a well-prepared candidate teacher The results indicated that the use of games facilitated meaningfully the improvement of vocabulary, which was reflected in the noticeable increase of the post-test scores and students’ progress during the intervention. In conclusion, this study helped students to improve their vocabulary learning, the researcher to sharpen her teaching skills and the community to have a well-prepared candidate teacher